Deyeuxia gaoligongensis (Poaceae: Agrostidinae), a new species from Gaoligong Shan in Yunnan, China - Paszko, Beata; Pendry, Colin (Phytotaxa, 2013)
Deyeuxia gaoligongensis, a new species from the Gaoligong Shan region of NW Yunnan, SW China, is described and illustrated. The new grass is morphologically similar to D. debilis, but differs from the latter by its well-developed lemma awn that is twisted at the base, geniculate, and inserted on the lower half of the back of the lemma.